Development of Teaching Materials to Support Learning of the Merdeka Curriculum on Thermochemistry Material Phase F SMA/MA - Rahmadhani, Melia; Mawardi, Mawardi; Okta Suryani; Reza Akmar (PT Inovasi Pratama Internasional, 2025)
This study aims to develop a teaching material on thermochemistry to support learning in Phase F SMA/MA Merdeka Curriculum. Educational Research Design (EDR) were used as the design approach and limited to prototyping stage. The subjects were three chemistry lecturers, two teachers who teach chemistry subjects and nine phase F students. Data was collected using validity and practicality questionnaires which resulted average content validity of 0.85 and construct validity of 0.87, where it can be classified as valid. Furthermore, the percentage of practicality is 96% for teachers and 94% for students, which can be classified as very practical. From these findings, it can be concluded that the developed teaching material is valid and practical.